Safe(r)-by-design principles in the thermoplastics industry: guidance on release assessment during manufacture of nano-enabled products - McLean, Polly; Hanlon, James; Salmatonidis, Apostolos; Galea, Karen S.; Brooker, Finlay; Citterio, Cristiano; Magni, Daniele; Vázquez-Campos, Socorro; Lotti, Davide; Boyles, Matthew S. P. (Frontiers in Public Health, 2024)
Background The application of nanomaterials (NMs) and nano-enabled products (NEPs) across many industries has been extensive and is still expanding decades after first being identified as an emerging technology. Additive manufacturing has been greatly impacted and has seen the benefits of integrating NMs within products. With the expansion of nanotechnology, there has been a need to develop more adaptive and responsive methods to ascertain risks and ensure technology is developed safely. The Safe(r)-by-Design (SbD) concept can be used to establish safe parameters and minimise risks during the materials’ lifecycle, including the early stages of the supply chain. Exposure monitoring has advanced in recent years with the creation of standardised protocols for occupational exposure assessment of nano-objects and their aggregates and agglomerates (NOAA). Methods To aid in the development of an online SbD-supporting platform by the EU-funded project SAbyNA, we adopt a Europe Standard for monitoring release of NOAA to identify if a greater release of NOAA is associated with incorporation of NMs within NEPs compared to a polymer matrix alone. Case studies included filaments of polypropylene (PP) with nano-Ag or polycarbonate (PC) with single-walled carbon nanotubes (SWCNTs). NMs were received in masterbatch, and therefore previously modified to align with SbD interventions. Results were collected in line with European Standard recommendations: monitoring particle concentrations using direct reading instruments (DRI), sampling for offline chemical and morphological analysis, and collecting contextual information. Results and discussion Based on the criteria described in the European standard (BS EN 17058), data from both case studies identified that inhalation exposure relating to NM was “unlikely”. Despite this, during the production of the SWCNT-PC filaments, some noteworthy observations were made, including several DRI activity measurements shown to be higher than background levels, and material morphologically similar to the reference SWCNT/polymeric masterbatch observed in offline analysis. The data collected during this campaign were used to discuss choices available for data interpretation and decision-making in the European Standard for monitoring release of NOAA and also to facilitate the development of SAbyNA’s user-friendly industry platform for the SbD of NMs and NEPs.